Analisis Kebutuhan Ruang Terbuka Hijau Pada Industri Keramik PT X - resa risanti; Aussie Amalia (Jurnal Serambi Engineering, 2024)
PT X is a ceramic industry, there are several stages, namely the powdering, pressing and firing stages, which generate emissions at each stage of the production process. Emissions from industrial activities can pollute the air around industrial sites. This pollution can be prevented and offset by management practices such as the provision of green open spaces. However, PT X does not yet have any green areas, which is very contrary to current regulations. Therefore, this study was conducted to analyse the need for green open space from the total area owned by PT X. In conducting the study, a quantitative descriptive method was used by conducting data analysis on primary and secondary data. The results of this study state that PT X is required to provide Green Open Space as a form of mitigation and fulfilment of legal obligations.